Grahame Clark's new archaeology : the Fenland Research Committee and Cambridge prehistory in the 1930s - Smith, Pamela Jane
The Fenland Research Committee, founded in 1932, guided research in the low wetlands north of Cambridge in east England. Its work marked a turning-point in the developing prehistory of Sir Grahame Clark, a change so profound it is here called a 'new archaeology'. A leading approach now as 'ecological archaeology', it is here shown to have its conception in certain goals, definitions, concepts, and assumptions Ñ and in the field circumstances which promoted a then-new approach to prehistoric materials.